AVALIAÇÃO DO CONFORTO E STRESS TÉRMICO EM UMA LAVANDERIA HOSPITALAR - Flesch, João Batista (Revista Liberato, 2013)
The present assignment intends to evaluate the hospital laundry from University Hospital in Porto Alegre, in terms of thermal comfort. The stages developed in this assignment were analysis of this industrial environment aiming to identify faulty points, proposals for improving this environment and evaluation of the thermal comfort, according to the in force rules. That environment contains people who work beside calanders used to dry and iron hospital clothes. The working place presents several surfaces with high temperatures, which generates a very hot working station. Preliminary data point out that the place is thermally unhealthy, with the WBGT rates much higher than the limits established for this activity, according to the norm NR 15 Atividades e Operações Insalubres [1978]. Some of the changes were implemented and their results measured. Some people heat changes modeling are also done, under the methodology proposed by Fanger (PMV and PPD) and the twonode model (DISC and TSEN), to establish thermal comfort rates. The comparison of the results shows that there was a significant improvement at the hospital laundry concerning the thermal comfort felt by those who work in this place. The new unhealthy thermal rate measured stayed within the tolerable according to the in force norm, which represents an important advance in the working conditions improvement at this working place.